Development and validation of the Japanese version of the Public Attitudes Toward Epilepsy (PATE‐J) Scale - Junichi Hatakeda; Hiroumi Shimazaki; Izumi Kuramochi; Takayuki Iwayama; Sayaka Kobayashi; Hideyuki Matsuki; Haruo Yoshimasu; Kheng Seang Lim (PCN Reports)
Abstract Aim This study aimed to develop and validate a Japanese version of the Public Attitudes Toward Epilepsy (PATE‐J) Scale to measure attitudes towards epilepsy among the general Japanese population. Methods The study employed a cross‐sectional design using an online survey of 537 participants from the general public in Japan, with follow‐up surveys at 2 weeks and 3 months. The PATE Scale was translated following standard guidelines and validated by conducting confirmatory factor analysis (CFA) on the complete data set to assess the original two‐factor structure of the PATE Scale. Internal consistency assessment, and convergent validity testing with the Modified Epilepsy Stigma Scale (M‐ESS), Perceived Devaluation Discrimination Scale (PDDS), and Epilepsy Knowledge Scale (EKS) were carried out. Results CFA confirmed the two‐factor structure of the PATE‐J, comprising “Personal Domain” and “General Domain.” The model showed acceptable fit indices (χ²(76) = 607.974, comparative fit index = 0.849, Tucker–Lewis index = 0.820, root‐mean‐square error of approximation = 0.114, standardized root‐mean‐square residual = 0.078) and high reliability (Cronbach's α = 0.87 for Personal Domain and 0.75 for General Domain). Strong correlations with the M‐ESS (r = 0.713, p < 0.001), and weaker correlations with the PDDS, along with a negative correlation with the EKS (r = −0.306, p < 0.001), highlighted the PATE‐J's distinctiveness. No significant associations were found between demographic factors and PATE‐J scores. Conclusion The PATE‐J demonstrates strong psychometric properties and cultural relevance for measuring public attitudes toward epilepsy in Japan. Its validated two‐factor structure supports cross‐cultural comparisons and provides a reliable tool for assessing public attitudes, informing interventions, and guiding education campaigns.